Scientific and practical aspects of preservation of architectural and urban heritage in the development of modern architectural and restoration education - Cherkasova , K. (New Collegium, 2021)
The historical, theoretical, scientific and practical aspects of architectural and restoration activities, which have observed in the aspect of the formation and development of architectural restoration education in Ukraine are considering within the article. Training issues of restoration specialists of real estate consideration is an important area of architectural higher education due to the need to replenish personnel for the development of scientific-, design- and professional activity spheres. The interdependence of the spheres of science, practice and education is a necessary condition for the preservation of cultural heritage, which currently exists as one of the important indicators of the state's cultural policy. The problem of mastering the architectural and urban planning heritage consists in the need to consider two opposing tendencies: the protection of the primary uniqueness of an architectural monument and the development of a historical urban environment with the involvement of modern architecture techniques, as a result of which historical authenticity is gradually lost and the urban environment is acquiring an increasingly universal and international character. In contemporary architectural design this problem is solved at the stage of developing urban planning documentation and detailed plans for the territory of historical areas, considering the system of restrictions on architectural and urban planning activities in the protection zones of cultural heritage objects of different use modes. The educational programs of the KhNUCEA Department of Reconstruction and Restoration of Architectural Objects have been developed considering professional competencies, aimed at mastering the world experience of achievements in the field of architectural and restoration education while maintaining the traditions that have developed over the years of the architectural education existence in Kharkov. The Department of Reconstruction and Restoration of Architectural Objects, formed in 1996, has united in its team specialists with experience in scientific and practical activities in the areas of urban planning restoration, restoration of architectural monuments, architectural archeology, reconstruction of historical objects.